2021
DOI: 10.25165/j.ijabe.20211401.5698
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ecosystem service of straw return to soil in a wheat field of China

Abstract: Crop straw is an important natural resource in China because it is rich in nutrients. When returned to fields after harvests, the straw can improve soil quality and the next crop's yield. Evaluating the economic values of the main ecological services of a farmland ecosystem while implementing the straw return technique can be a more systematic and comprehensive approach to better understand the contribution of straw return to the development of ecological agriculture. Based on the data of a field experiment es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that after the combined pretreatment, the lignin of the CP group was significantly reduced, and there was almost no loss of cellulose and hemicellulose (Table 6). During the aerobic hydrolysis process, due to the removal of lignin, more cellulose was hydrolyzed, resulting in higher reducing sugar content in the CP group than in the CK group in the early stage of anaerobic fermentation [31] . The changing trend of reducing sugar content in each experimental group was roughly the same.…”
Section: Effect Of Combined Pretreatment On Anaerobic Fermentation Ch...mentioning
confidence: 99%
“…It is worth mentioning that after the combined pretreatment, the lignin of the CP group was significantly reduced, and there was almost no loss of cellulose and hemicellulose (Table 6). During the aerobic hydrolysis process, due to the removal of lignin, more cellulose was hydrolyzed, resulting in higher reducing sugar content in the CP group than in the CK group in the early stage of anaerobic fermentation [31] . The changing trend of reducing sugar content in each experimental group was roughly the same.…”
Section: Effect Of Combined Pretreatment On Anaerobic Fermentation Ch...mentioning
confidence: 99%
“…The burning of straw produces a large amount of PM 2.5 (Chen et al 2016) and can cause serious environmental pollution (Xiao 2012). Straw reincorporation has become a prevailing agricultural practice for improving soil fertility and reducing air pollution induced by crop straw burning (Cui et al 2021). It is well stablished that straw applied directly to the soil increases soil fertility and nutrient substrates for microbial attachment (Zhou et al 2016), stimulates the activity of soil heterotrophic microorganisms (Cai et al 2003), promotes the absorption of nutrients by the root system, and increases maize yield (Qin et al 2015; Zhang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The major limitations for the large-scale application of biomass are related to its diverse physical and chemical properties, as well as the availability of seasonal and geographical patterns. At present, due to the presence of some restrictive factors, China faces the issue regarding excessive production of straws, and the issue is further complicated by burning straws in agricultural fields . A previous study reported that China’s animal husbandry has rapidly developed over the recent two decades, indicating that a great amount of animal manure has been produced accordingly .…”
Section: Introductionmentioning
confidence: 99%
“…At present, due to the presence of some restrictive factors, China faces the issue regarding excessive production of straws, and the issue is further complicated by burning straws in agricultural fields. 6 A previous study reported that China's animal husbandry has rapidly developed over the recent two decades, indicating that a great amount of animal manure has been produced accordingly. 7 Animal manure, containing N, P, K, and other valuable nutrients, is an excellent biofertilizer and raw material for producing bioenergy.…”
Section: Introductionmentioning
confidence: 99%